2002
DOI: 10.1177/026119290203000204
|View full text |Cite
|
Sign up to set email alerts
|

The ECVAM International Validation Study on In Vitro Embryotoxicity Tests: Results of the Definitive Phase and Evaluation of Prediction Models

Abstract: From 1996 to 2000, ZEBET (Centre for Documentation and Evaluation of Alternative Methods to Animal Experiments at the BgVV, Berlin, Germany) coordinated the European Centre for the Validation of Alternative Methods (ECVAM) prevalidation and validation study on three embryotoxicity tests: a) a test employing embryonic stem cell lines (EST); b) the micromass (MM) test; and c) the postimplantation rat whole-embryo culture assay (WEC test). The main objectives of the study were to assess the performance of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
228
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(235 citation statements)
references
References 19 publications
5
228
0
2
Order By: Relevance
“…Whole embryo cell cultures show gene expression patterns very similar, over time, to in utero embryos; and, in the case of rat, cultures are matching to a great extent the gene expression profile in human embryos undergoing neurulation and early embryogenesis (Robinson et al, 2012b). Therefore, given the high in vivo translation potential of whole embryo cell cultures (Genschow et al, 2002), the results can benefit of better support for a possible in vivo extrapolation. However, whole embryos display tissue heterogeneity, which may mask some changes in specific tissues or cells (Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whole embryo cell cultures show gene expression patterns very similar, over time, to in utero embryos; and, in the case of rat, cultures are matching to a great extent the gene expression profile in human embryos undergoing neurulation and early embryogenesis (Robinson et al, 2012b). Therefore, given the high in vivo translation potential of whole embryo cell cultures (Genschow et al, 2002), the results can benefit of better support for a possible in vivo extrapolation. However, whole embryos display tissue heterogeneity, which may mask some changes in specific tissues or cells (Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…In this experiment whole embryo mouse cultures were performed on four control embryos and four ethanol-treated ones, the latter characterized by a phenotype of open neural tubes (Wang et al, 2008). Transcriptomic studies suggest that teratogenic effects observed in whole embryo cultures are relevant to previously identified mechanisms of toxicity in vivo (Genschow et al, 2002;Luijten et al, 2010;Zhou et al, 2011).…”
mentioning
confidence: 99%
“…Overall accuracy of 70% (Genschow et al, 2002) Foeniculum vulgare L. (no teratogenicity) (Ostad et al, 2004) Mammalian whole embryo culture test (WEC) Embryos are isolated on day 10 of gestation and cultured for 48 h; morphological, developmental, functional and growth parameters are measured…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Overall accuracy of 80% (Genschow et al, 2002) Dihydroartemisinin primarily affects primitive red blood cells, causing subsequent tissue damage and dysmorphogenesis (Longo et al, 2006) Methods based on embryos of lower order species Frog embryo teratogenesis assay -Xenopus (FETAX) During the first 96 h Xenopus embryos development parallels many of the major processes of human organogenesis (Measurement of mortality, malformation, and growth inhibition)…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Despite validation studies reporting a relatively promising predictive efficiency of this assay compared to other in vitro models (i.e. correct classification of 78% of well-characterized compounds into the categories of non-embryotoxic, weakly embryotoxic and strongly embryotoxic compounds) (80), this test is limited in its ability to predict drug toxicity profiles for human diseases. Species-specific pharmacokinetic profiles frequently do not address the metabolism or the genetic diversity of patients living in heterogeneous conditions, thereby giving rise to drug-induced responses that may be clinically irrelevant in humans.…”
Section: Hipscs For Drug Toxicology Assessmentmentioning
confidence: 99%